BLOOD GLUCOSE LEVELS AND SALIVARY BACTERIAL PROFILE AMONG PATIENTS WITH DIABETES MELLITUS: A DESCRIPTIVE CROSS-SECTIONAL STUDY - Ida Ayu Made Sri Arjani; I Nyoman Gede Suyasa; I Nyoman Jirna; Nyoman Mastra; Cok Dewi Widhya Hana Sundari; Nursinta Riswandani (Meditory : The Journal of Medical Laboratory, 2026)
Background: Diabetes mellitus (DM) is a chronic non-communicable disease characterized by prolonged hyperglycemia, which can increase salivary glucose levels and reduce salivary flow, thereby promoting bacterial growth and increasing the risk of oral infections. Objective: To describe fasting blood glucose levels, salivary bacterial counts, and the Gram-staining characteristics of salivary bacteria among patients with diabetes mellitus. Methods: This cross-sectional correlational study involved 32 diabetes mellitus patients selected using accidental sampling. Data were collected through questionnaires, fasting blood glucose measurement using POCT, salivary bacterial count using the TPC method, and Gram staining. Results: All participants (100%) had fasting blood glucose levels within the diabetic range (≥126 mg/dL), indicating persistent hyperglycemia. Likewise, all saliva samples showed high bacterial counts (>100,000 CFU/mL). Gram-positive bacteria were more predominant than Gram-negative bacteria, accounting for 55.2% and 44.8% of the bacterial isolates, respectively. Conclusions: Patients with diabetes mellitus exhibited persistent hyperglycemia, high salivary bacterial counts, and a predominance of Gram-positive bacteria. These findings provide baseline information on the salivary bacterial profile of patients with diabetes mellitus and emphasize the importance of maintaining glycemic control and oral hygiene as part of comprehensive diabetes care.